A Comparison of Monoculture and Polyculture of Nile Tilapia (Oreochromis niloticus) with Carps and Sahar (Tor putitora) - Pandit, Narayan P.; Ranjan, Rahul; Shrestha, Madhav K. (Nepalese Journal of Aquaculture and Fisheries, 2023)
Addition of Nile tilapia (Oreochromis niloticus) and sahar (Tor putitora) in carp-polyculture, and tilapia monoculture systems was tested. The experiment was conducted at the Agriculture and Forestry University, Chitwan, Nepal in 12 earthen ponds of 150 m2 for 185 days. The experiment was conducted in a completely random design with four treatments in triplicate: a) Carp-polyculture (10,000/ha) + mixed-sex tilapia (3,000/ha) + sahar (1,000/ha) (T1); b) Carp-polyculture + monosex tilapia (3,000/ha) (T2); c) Monosex tilapia at 10,000/ha with fertilization only (T3); and d) Monosex tilapia at 20,000/ha with fertilization and feeding (T4). Silver carp, bighead carp, common carp, grass carp, rohu and mrigal were stocked in all ponds as of normal practice. The ponds were fertilized weekly with urea and DAP. Fish were fed daily with 26% CP feed at 2% body weight. Combined net fish yield was significantly higher (p<0.05) in T4 (3.77±0.23 t/ha/crop) compared to T3 (1.03±0.14 t/ha/crop); there was no significant difference among T1 (2.82±0.23 t/ha/crop), T2 (3.20±0.17 t/ha/crop) and T4 (3.77±0.23 t/ha/crop). The mean harvest size, daily growth, GFY and NFY of monosex Nile tilapia in T4 were significantly higher than in T3. The gross profit was significantly higher in T4 compared to T3 without any significant difference between T1 and T2.